West-East Convergence in the Prevalence of Illicit Drugs: Socioeconomics or Culture? - Harald Tauchmann (Kiel Institute for the World Economy (IfW), 2008)
In contrast to West-Germany, illicit drugs were virtually absent in the East-Germany until 1990. Yet, after the collapse of the former GDR, East-Germany was expected to encounter a sharp increase in the prevalence of substance abuse. By analyzing individual data, we find that East-Germany largely caught up with West-Germany?s ever-growing prevalence of illicit drugs within a single decade. We decompose the west-east difference in prevalence rates into an explained and an unexplained part using a modified Blinder-Oaxaca procedure. This decomposition suggests that the observed convergence is just weakly related to socioeconomic characteristics and therefore remains mainly unexplained. That is, West- and East-Germans seem to have become more alike per se. We conclude that both parts of the country have converged in terms of the culture of drug consumption.
Keywords: I12; P23; P36; 330; illicit drugs; west-east convergence; decomposition; Drogenkonsum; Entwicklungskonvergenz; Dekompositionsverfahren; Schätzung; Neue Bundesländer; Alte Bundesländer; Deutschland